(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
As nations develop and their economies grow bigger, social problems also intensify. One great concern deals with peace and order as well as the safety and security of the people. Various psychologists would render different explanations to the cases of crimes, but what is apparent even to the most innocent individual is that crimes are everywhere. Anyone can be a victim of crime, which fosters fear in a lot of people. Knowing their responsibility, the governments of different nations have launched various innovations on how to prevent crimes. One of these innovations is the use of CCTV. The study revealed that the CCTV camera was a highly effective tool in monitoring suspicious activities, improved general security, including safety around properties, helped to identify offenders, and was used to apprehend criminals. Closed Circuit Television (CCTV) cameras have recently become an indispensable part of daily life. Cameras are of vital importance as significant elements of security systems in different buildings and establishments such as houses, stores, and shopping malls. Also, millions of CCTV cameras are installed on streets with the goal of reducing crimes, preventing crimes, and increasing public safety.